Studies on the changes in rectal permeability and intestinal microbiota with developmental age in young rats - Luo, Yunfeng; Luo, Liangming; Xia, Mengle; Liu, Qian; Zhang, Guosong (Frontiers in Microbiology, 2025)
IntroductionThe gut contains a diverse array of commensal microorganisms, forming a vital biological barrier within the intestine that contributes to the overall intestinal mucosal barrier. However, research on the rectal barrier during early development remains limited. This study aims to investigate the relationship between intestinal microbiota and rectal barrier function in young rats.MethodsWe evaluated the rectal barrier structure and function in rats at 2-, 4-, and 10-week-old. Methodology included histological analysis, Muc2 expression quantification, immunofluorescence localization of tight junction proteins (ZO-1, Occludin, Claudins), blood glucose monitoring after rectal insulin administration, and 16S rDNA sequencing of rectal microbiota. Spearman correlation analysis was used to explore mechanisms linking age-dependent changes in rectal permeability to microbiota dynamics.ResultsPhysiological rectal permeability was significantly higher in 2-week-old rats compared to 4- and 10-week-old rats (p < 0.01), although systemic biomarkers (LPS, D-LA, and LBP) showed no significant differences. The rectal microbiota exhibited marked age-dependent shifts in composition, α/β-diversity, and metabolic pathways, with increased abundance of beneficial taxa (e.g., Muribaculaceae, Akkermansia) in older rats. Correlation analysis revealed strong associations between reduced permeability, elevated Occludin expression, and microbiota maturation (R = 0.65, p < 0.001).ConclusionThis study demonstrates that age-dependent maturation of the rectal barrier is closely linked to microbiota composition and tight junction protein expression, providing insights into developmental mechanisms and potential strategies for pediatric rectal drug delivery.